Gypenosides alleviates HaCaT keratinocyte hyperproliferation and ameliorates imiquimod-induced psoriasis in mice - Liu, Tao; He, Yuanmin; Liao, Yongmei (Allergologia et Immunopathologia, 2024)
Background: Psoriasis is an autoimmune skin condition characterized by hyperproliferation of keratinocytes and chronic immune responses. Gypenosides (Gyp) exhibits anti-proliferative and anti-inflammatory effects on different diseases. However, its functioning and mechanism of Gyp on psoriasis remains unknown.Objective: To explore the effect and mechanism of Gyp on psoriasis.Material and Methods: The impact and mechanism of Gyp on psoriasis in vitro and in vivo were probed through cell counting kit-8 (CCK-8), 5-ethynyl-2′-deoxyuridine (EdU) incorporation assay, reverse transcription quantitative polymerase chain reaction, hematoxylin and eosin staining, enzyme-linked immunosorbent serologic assay, immunofluorescence, and Western Blotting assays.Results: Gyp inhibited cell proliferation and the release of inflammatory cytokinesin interleukin (IL-22)-induced spontaneously transformed human aneuploid immortal keratinocyte cell line (HaCaT). In addition, Gyp demonstrated enhancement in erythema and scaling as well as reductions in the thickness of epidermal layers, release of inflammatory factors, and Ki-67 (a nuclear protein) level in imiquimod (IMQ)-induced mice. Mechanistically, Gyp upregulated nuclear factor erythroid 2-related factor 2 (Nrf-2) expression and diminished the level of p-p65/p65 and p-STAT3/STAT3 in skin tissues from IMQ-induced mice and IL-22-induced HaCaT cells, which were reversed with the application of ML385, an inhibitor of Nrf2. In addition, the administration of ML385 reversed decrease in cell viability and reduced the expressions of IL-1β, IL-6, and tumor necrosis factor-α (TNF-α) in IL-22-induced HaCaT cells caused by Gyp.Conclusion: In summary, Gyp reduced excessive cell growth and inflammation in psoriasis by suppressing nuclear factor kappa B (NF-κB) and signal transducer and activator of transcription 3 (STAT3) through activation of Nrf2.